Examining the feasibility and preliminary effects of resistance exercise training and creatine supplementation in individuals treated for colorectal cancer - Ciaran M. Fairman; Alex M. Brooks; Darren G. Candow; Kylah E. Jackson; Genevieve Bottone; Brett Scott; Kenneth S. Anderson; Katie R. Hirsch; Thomas D. Cardaci; Brandon N. VanderVeen; Christine E. Blake; Tiejun Zhang; et al. (PLoS ONE, 2026)
Purpose The purpose of this trial was to assess the feasibility, acceptability and safety of a 10-week hybrid (in-clinic and virtual) resistance exercise training RET program with or without CrM in individuals treated for colorectal cancer. Methods Twenty-seven participants were randomized to RET plus 5 grams/day of CrM (EXSUPP; n = 13) or 5 grams/day corn-starch maltodextrin placebo (EXPLA; n = 14). RET was performed three times per week. Feasibility was assessed through recruitment, retention and fidelity (percentage of prescribed RET and supplementation completed). Acceptability was evaluated using a 5-point Likert scale, and safety was monitored through adverse event reporting. Secondary outcomes (body composition, muscular strength, physical function) were assessed pre- and post-intervention using baseline-adjusted ANCOVA models and focus group interviews. Results Registry-based recruitment identified 1378 potentially eligible individuals and 27 of 410 assessed (6.6%) enrolled, highlighting recruitment challenges. Retention was high (24/27; 88.9%). Adherence to RET and supplementation was strong (both > 85%) with no serious adverse events reported. Participants reported high acceptability for both in person and virtual components. No significant between group differences were observed for secondary outcomes; however, both groups demonstrated modest improvements in muscular strength and short physical performance battery (SPPB) scores. Conclusions A hybrid RET program with CrM was feasible, acceptable and well tolerated in individuals with colorectal cancer who were previously treated with chemotherapy. Implications for Cancer Survivors Hybrid supervised RET is safe, acceptable, and associated with modest improvements in strength and physical function among individuals treated for colorectal cancer. While creatine supplementation did not demonstrate clear additive effects in this pilot trial, further adequately powered studies are warranted. Trial Registration: NCT06420726.